Desain dan Implementasi Sistem Online Gudang Pada PT. PLN (Persero) Distribusi Regional Jawa Tengah dan D.I Yogyakarta - Ervin Adhi Cahyanugraha; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
The information system that can provide complete, accurate information in an integrated way with the ability to reach all people in the system is very important. The criteria are not fulfilled by the warehouse management system on PT. PLN (Persero), distribution of Central Java and Special Region of Yogyakarta. Some districts are not reached by the information system technology; some of them still use Microsoft Office Excel to manage the goods in the warehouse. . So, communication up to rayon is not good, rayon and area are so hard to exchange information, transaction between rayon and area is not quick. this case cause procurement goods is hampered, and this make direct impact to unfinished project . Therefore, the online system of this warehouse can solve the flaw of the old system. The Warehouse Online System is the ASP.Net-based web application. This development process uses Microsoft Visual Studio as the development tools. An information system is not separable from the database as the information data storage; Warehouse Online System uses Oracle as the Relational Database Management System (RDBMS). The Warehouse Online System is suitable with the Standard Operational Procedure (SOP) of PT. PLN (Persero). Through Warehouse Online System, the distributors from the area or district can be integrated to communicate, to do the transaction on the material in the warehouse, and to get the access of the user based on their task and authority. Based on the Black Box test, the functions on Warehouse Online System function like what is expected. The maintenance process is still needed to improve the system in the future.